Multyparametric MRI in differential diagnosis of epithelial ovarian tumors - Julia V. Nosova; Alina E. Solopova; Grigorii N. Khabas (IP Berlin A.V., 2020)
Systematic analysis of publications concerning differential diagnosis of epithelial ovarian tumors has been done. Review includes articles published in MEDLINE, PubMed, Cochrane Collaboration Registry of Controlled Trials over the last 10 years. The objective of this study was to evaluate the ability of MRI with quantitative perfusion (DCE) and diffusion analysis (DWI) for preoperative differential diagnosis of indeterminate ovarian tumors. DCE-MRI parameters and ADC may represent imaging biomarkers for predicting the nature of ovarian tumors. Authors now recommend that for complex cystic or cystic-solid masses, both DWI and DCE MRI are used, if available.